Blood‐Brain Barrier Permeable Gold Nanoparticles: An Efficient Delivery Platform for Enhanced Malignant Glioma Therapy and Imaging. Issue 24 (8th August 2014) - Cheng, Yu; Dai, Qing; Morshed, Ramin A.; Fan, Xiaobing; Wegscheid, Michelle L.; Wainwright, Derek A.; Han, Yu; Zhang, Lingjiao; Auffinger, Brenda; Tobias, Alex L.; Rincón, Esther; Thaci, Bart; et al.
<x xml:space="preserve">Abstract</x> The blood‐brain barrier (BBB) remains a formidable obstacle in medicine, preventing efficient penetration of chemotherapeutic and diagnostic agents to malignant gliomas. Here, a transactivator of transcription (TAT) peptide‐modified gold nanoparticle platform (TAT‐Au NP) with a 5 nm core size is demonstrated to be capable of crossing the BBB efficiently and delivering cargoes such as the anticancer drug doxorubicin (Dox) and Gd3+ contrast agents to brain tumor tissues. Treatment of mice bearing intracranial glioma xenografts with pH‐sensitive Dox‐conjugated TAT‐Au NPs via a single intravenous administration leads to significant survival benefit when compared to the free Dox. Furthermore, it is demonstrated that TAT‐Au NPs are capable of delivering Gd3+ chelates for enhanced brain tumor imaging with a prolonged retention time of Gd3+ when compared to the free Gd3+ chelates. Collectively, these results show promising applications of the TAT‐Au NPs for enhanced malignant brain tumor therapy and non‐invasive imaging.